Wood Anatomy of Indian Myristicaceae with Critical Remarks on some foreign Genera - Vijendra Rao, R.; Dayal, R.; Raturi, R. D. (Indian Forester, 1992)
Wood Anatomy of the Indian Myristicaceae viz. Gymnacranthera, Horsfieldia, Knema and Myristica has been described in detail. The study indicates that the four Indian genera can be easily distinguished from each other on the basis of their wood structure. Woods of some foreign genera both African and American have also been investigated for a better understanding of their relationship with the Asiatic members Of the family and to confirm certain observations made by earlier workers. The occurrences of reticulate, irregular anastomosing type of vesselperforations in Pycnanthus and scalariform type in Cephalosphaera (both African genera) has been recorded for the first time Observations also show that oil cells and crystals in the rays are completely lacking in the, African and Indian representatives. Other observations which are contrary or in agreement to the findings of the earlier workers have also been recorded.